Regional Public Goods, Spillovers and Optimizing Federal Subsidies - D.A. Vardy (Queen's University, Department of Economics, 1971)
The purpose of the present paper is to provide an integrated analysis of federal aid through the development of a set of fiscal models for a decentralized government. Federal subsidies will be shown to be instruments of economic policy where such policy is directed toward correction for external effects and non-neutrality of the fiscal system.
Keywords: 330